FastIC: a fast integrated circuit for the readout of high performance detectors. (1st May 2022) - Gómez, S.; Alozy, J.; Campbell, M.; Fernandez-Tenllado, J.M.; Manera, R.; Mauricio, J.; Pujol, C.; Sanchez, D.; Sanmukh, A.; Sanuy, A.; Ballabriga, R.; Gascon, D.
Abstract: This work presents the 8-channel FastIC ASIC developed in CMOS 65 nm technology suitable for the readout of positive and negative polarity sensors in high energy physics experiments, Cherenkov detectors and time-of-flight systems. The front-end can be configured to perform analog summation of up to 4 single-ended channels before discrimination in view of improving time resolution when segmenting a SiPM. The outputs encode the time-of-arrival information and linear energy measurement which captures the peak amplitude of the input signal in the 5 µA–25 mA input peak current range. Power consumption of the ASIC is 12 mW/ch with default settings. Measurements of single photon time resolution with a red-light laser source and a HPK SiPM S13360-3050CS are ≈140 ps FWHM.